2020
DOI: 10.1080/16549716.2020.1863128
|View full text |Cite
|
Sign up to set email alerts
|

Keeping silent or running away. The voices of Vietnamese women survivors of Intimate Partner Violence

Abstract: Background: Legislative initiatives have been implemented to fight against Intimate Partner Violence (IPV) and offer protection to its survivors in Vietnam. However, this type of violence is relatively common in the country, where broader structural inequalities, like poverty and the system of male dominance, increase women's vulnerability to IPV. Objective: This study aimed to explore the strategies that Vietnamese IPV survivors take to cope with the abuse from their partners and maximize their safety and wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Only four sessions of FGD were conducted in four communities in Ibadan, and five were conducted in five communities in Lagos. The age range of the female adolescent participants was (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), more than three-quarters of the participants were below 19 years, while the rest were above 20 years. The majority of the adolescents were apprentices while the rest were students, with the highest education having secondary school certificates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only four sessions of FGD were conducted in four communities in Ibadan, and five were conducted in five communities in Lagos. The age range of the female adolescent participants was (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), more than three-quarters of the participants were below 19 years, while the rest were above 20 years. The majority of the adolescents were apprentices while the rest were students, with the highest education having secondary school certificates.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, it is the act of keeping an unspoken agreement not to speak about what happened to them"survivor [15]. Not only in Nigeria, but also in other contexts, adolescents and young women find it difficult to speak out due to shame, stigma, and some socio-culturally shaped ideation [16] about retaliation effects on the survivors [17,18]. In addition, depending on the relation to the state, there is also a perceived notion of a lack of confidence in the state agencies, including the healthcare systems [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…This research theme remains a neglected topic in Vietnam, as only several qualitative studies have investigated the complex set of structural factors (e.g. poverty, culture, social stigma, and women subordination) on IPV victimisation (Dao et al, 2012;Herrero-Arias et al, 2021). "How do environmental and family contexts shape children's developmental outcomes over time?"…”
Section: Neighbourhood Disorders: Reflecting Sense Of Communitymentioning
confidence: 99%
“…Øverup et al (2017) found that individuals with higher controlled orientation are more likely to perpetrate IPV. Previous studies have suggested that controlled orientation may be a risk factor for IPV perpetration, while autonomous orientation may be a protective factor (Deci & Ryan, 2002; Hove et al, 2010). For impersonal orientation, we did not take it into account in the present study because impersonal orientation is related to apathy and not related to perpetrating IPV (Øverup et al, 2017).…”
Section: Introductionmentioning
confidence: 99%